Povezave med jakostjo mišic spodnjih okončin in hitrostjo pri linearnih in zavitih sprintih - Fink, Mojca (Šport (Ljubljana), 2024)
The study was designed to investigate the associations between the isometric strength of selected muscle groups and the speed of linear and curvilinear sprints. Eighteen subjects (12 males (mean age: 24,8 ± 4,7 years) and 6 females (mean age: 20 ± 1,3 let)) participated in the study. Subjects performed linear and curvilinear sprints at the first visit and strength measurements at the second visit (knee extensors and flexors strength, hip adductors and abductors strength). The relationship between lower limb strength and maximum sprint speed was assessed using Pearson's correlation coefficient. Linear regression was performed to predict maximum speed in both linear and curvilinear sprints based on the strength variables. Knee flexors and extensors strength and hip adductors strength were in significant moderate to high correlation with the maximum speed of linear and curvilinear sprints (r = 0,57 – 0,76), while hip abductors strength were correlated just with maximum speed of curvilinea.
Keywords: curvilinear sprint; hitrost; linear sprint; linearni sprint; mišična jakost; muscle strength; speed; zaviti sprint